O ensino da odontologia no Brasil: concepções e agentes - QUEIROZ, Maria Goretti (2006)
The aim of this documental exploratory study was to investigate the evolution of dental education in Brazil based on three main organizations: the Pan American Health Organization (PAHO), the Kellogg Foundation (KF) and the Brazilian Dental Education Association (BDEA). The study covers the period since the institutionalization of dental education in Brazil in 1856, until the National Curriculum Guidelines for Undergraduate Courses in 2002. References: high education and health education legislation, the history of high education in Brazil, and PAHO, KF and BDEA documents and recommendations about health human resources. Changes until 1961 were determined by government and were not attended by professional categories. Education was not in accordance with norms and disciplines were not homogeneous in different courses despite of the existence of legislation. In 1961, the Education Basis and Guidelines law, some distortions were amended. Universitary Reform in 1968, influenced by the North-American model, introduced changes like modernization of high education, and inclusion of levels of education in Dentistry. Learning and practice models had structural limits due to high costs and difficulties for implementation. Many interventions tried to adjust dental education to the regional and national scenario and to include Dentistry in the health area. It must be highlighted the importance of the National Curriculum Guidelines for Undergraduate Courses, as a result of the Viña del Mar Seminar (1955), and the involvement of PAHO, KF and BDEA in this process. The collective construction of the National Curriculum Guidelines emphasized the need of an effective public health system and professional education in accordance with public services. Different protagonists and concepts originated many discussions and tensions, often not understudied by professionals. Concepts and political and pedagogical projects in dental education need to be more cleared and professional categories must lead the construction of a new dentist and reinforcement of the Sanitary Reform. Local and regional disparities also may be taken into account in this process. Dental profession must also conduct discussion about dental personnel, including auxiliary dental professionals